2002
DOI: 10.1007/s001220200013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for resistance against Yellow rust in two wheat-derived recombinant inbred line populations

Abstract: Yellow rust, which is a major disease in areas where cool temperatures prevail, can strongly influence grain yield. To control this disease, breeders have extensively used major specific resistance genes. Unfortunately this kind of resistance is rapidly lost due to pathogen adaptation. More-durable resistance against yellow rust can be achieved using quantitative resistance derived from cultivars with well-established durable resistance. The winter wheat Camp Remy has maintained a high level of resistance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
94
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 42 publications
1
94
0
1
Order By: Relevance
“…Mallard et al (2005) attributed between 20 and 40% of the phenotypic variance to QYr.inra-2AL, which is comparable to the phenotypic variance explained by QYr.ufs-2A. In the study of Boukhatem et al (2002), QYR2 accounted for only 15.4% of the phenotypic variation. Bariana et al (2010) identified an APR QTL proximal to the region defining QYr.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Mallard et al (2005) attributed between 20 and 40% of the phenotypic variance to QYr.inra-2AL, which is comparable to the phenotypic variance explained by QYr.ufs-2A. In the study of Boukhatem et al (2002), QYR2 accounted for only 15.4% of the phenotypic variation. Bariana et al (2010) identified an APR QTL proximal to the region defining QYr.…”
Section: Discussionmentioning
confidence: 57%
“…While up to 75.2% of the variation seen for RT was explained by the QTL identified, only 60.4% of the variation seen for LAI was explained. Although heavy selection pressure for adult plant stripe rust resistance was imposed during the development and selection of Yr16DH70, minor QTL and QTL where expression is heavily influenced by environmental factors (Boukhatem et al 2002), may not have been retained in Yr16DH70. This may account for the consistently, but marginally higher disease rating obtained for Yr16DH70 compared to Cappelle-Desprez in each year of testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some significant DArT markers proved to be associated with known YR resistance genes, such as Yr24 at 1B, which is allelic to Yr26 and closely linked to barc187 (Li et al 2006) (Figure 2a). Boukhatem et al (2002) identified two major QTL for durable YR resistance on chromosome 2B, of which one was present in Opata 85 and mapped near the SSR marker gwm410. This marker is also present in LDb3 with wPt7757, which is significantly associated with YR ( Figure 2b, Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Yr30, at 3BS, has been reported to be linked to Sr2 and Lr27, and to SSR marker gwm533 (Spielmeyer et al 2003), and may be marked by wPt0995 and other DArT markers at LDb3 (Figure 2c) (it is present in Opata 85 and Pavon F76, included in this study). Singh et al (2000) and Boukhatem et al (2002) identified a region on chromosome 3DS associated with YR in Opata 85, which could have been identified by wPt1336 and wP19401.…”
Section: Discussionmentioning
confidence: 99%